Logics and Enablers of Transformative Innovation Policies: The case of the Colombian Appropriation of Science and Technology Policy - Pinzón-Camargo, Mario A.; Centeno, Juan Pablo; Andrade-Sastoque, Ernesto; Ordoñez-Matamoros, Hector Gonzalo (Novation, 2023)
In this work, we seek to answer the question, what are the main logics and enablers underlying the implementation of TIP policies in countries of the Global South? We address this question using the Path-transformative heuristic (Pinzón-Camargo et al., 2020; Pinzón-Camargo, 2022). This heuristic combines two approaches, path dependency and institutional entrepreneurship theories, to explain the processes, decisions, and actions carried by actors in building an alternative path and how they face internal and external pressures that could support or damage their processes. Using an illustrative case based on the Colombian Social Appropriation of Science, Technology and Innovation policy, we examine in-depth interviews and secondary data on the underlying logics and enablers of innovation policies with transformative potential. This work allows us to identify six underlying logics in three of the four phases of the Path-transformative heuristic and six enablers extended through all the transformative pathway. Those elements bring a starting point to unfold and better understand TIP in the Global South.